Some personality characteristics of Stutterers - J, Bharath Raj; N, Pranesha Rao (Journal of All India Institute of Speech and Hearing, 1970)
Although the study of personality characteristics of stutterers has occupied the interest of many clinicians, since long past from now, there are comparatively few studies made in this area. As early as 1942, comparing a large group of college male stutterers with a controlled group, matched for age, intelligence and socio-economic status, Bender (1942) found that stutterers showed a greater tendency towards introversion and neuroticism, were less dominant in their interpersonal relationships, were less sociable and expressed less self-confidence. From his study Schultz (1947) came to similar conclusions, with a predominance on traits like submissiveness, inhibition, and hypersensitivity. A number of studies made in 1950’s as those of Pizzat (1951), Dahlstrom and Craven (1952), Boland (1953) and Walnut (1954), all of which used M.M.P.I., showed close agreement in their findings that stutterers showed lesser adjustment than non- stutterers, although on average their scores fell within the normal range. However, Walnut’s study indicated paranoid and depressive tendencies on the part of the stutterers and a tendency to react abnormally to speech and speaking situations. Summarising the results of research studies up to 1957, by the use of projective tests, M.M.P.I., etc., Goodstein (1958) comes to the conclusion that the findings from such studies have been conflicting and do not provide any significant difference between stutterers and non-stutterers, in terms of severe maladjustment or possession of a typical personality pattern unique to stutterers